A Correlational Study of Acute Stress and Resilience Among Hospitalized Burn Victims Following the Taiwan Formosa Fun Coast Explosion. (November 2020) - Chen, Ya-Lin; Lu, Ming-Hsiu; Weng, Ling-Tzu; Lin, Chin; Huang, Ping-Wei; Wang, Chih-Hsin; Pan, Hsueh-Hsing
Although the survival rate of burn patients in the Formosa Fun Coast Explosion disaster increased significantly, for patients facing long-term rehabilitation, there remained great stress. Therefore, the aim of this study was to explore the predictors of resilience among burn patients in this major disaster. We conducted a cross-sectional, descriptive study in a medical center in northern Taiwan, with a total of 30 burn patients enrolled. Patients' demographics were collected, and the Resilience Scale and Perceived Stress Scale were administered. Multivariate statistical analysis by stepwise and linear regression was used to test these predictors of resilience. The results showed that perceived stress was the key predictor of resilience in the stepwise regression analysis and by adjusting variables including stress level, gender, and education level. These results indicate that the stress level of burn patients should be determined first to provide more targeted methods for reducing stress and improving resilience.